The Anti-Trafficking Cause: From exceptionalism to shared struggle - Baskin, Sienna; Hewitt, Huey (Anti-Trafficking Review, 2020)
Response to the ATR debate proposition ‘It is worth undermining the anti-trafficking cause in order to more directly challenge the systems producing everyday abuses within the global economy.’